Do Regulation And Institutional Design Matter For Infrastructure Sector Performance ? - Andrés, Luis 2020- (The World Bank, 2007)
This paper evaluates the impact of economic regulation on infrastructure sector outcomes. It tests the impact of regulation from three different angles: aligning costs with tariffs and firm profitability; reducing opportunistic renegotiation; and measuring the effects on productivity, quality of service, coverage, and prices. The analysis uses an extensive data set of about 1,000 infrastructure concessions granted in Latin America from the late 1980s to the early 2000s. The analysis finds that as the theory indicates, regulation matters. The empirical work here reported shows that in three relevant economic aspects-aligning costs and tariffs; dissuading renegotiations; and improving productivity, quality of service, coverage, and tariffs-the structure, institutions, and procedures of regulation matter. Thus, significant efforts should continue to be made to improve the structure, quality, and institutionality of regulation. Regulation matters for protecting both consumers and investors, for aligning closely financial returns and the costs of capital, and for capturing higher levels of benefits from the provision of infrastructure services by the private sector